Guidebook on Molecular Modeling in Drug Design - N Claude Cohen (Academic Press, 1996)
Molecular modeling has assumed an important role in understanding the three-dimensional aspects of specificity in drug-receptor interactions at the molecular level. Well-established in pharmaceutical research, molecular modeling offers unprecedented opportunities for assisting medicinal chemists in the design of new therapeutic agents.